Mary Ann F. answered • 01/18/15

Math & Science... Algebra and Geometry specialist

Hi Marie -

The process of completing the square is pretty simple: Start by moving the constant term to the other side of the equals sign by adding 3 to both sides. Then we have this:

x

^{2}+ 2x + ___ = 3Now divide the coefficient on the x term in half and then square the result. This is what your constant term is in a perfect square trinomial.

In your problem, the coefficient on the x term is 2. Divide it in half and square the result:

2/2 = 1, and 1

^{2}= 1 << this is what I add to create a perfect square. But if I add it to one side, I have to add it to the other to keep the equation balanced:(x

^{2}+ 2x + 1) = 3 + 1Now let's change the notation a bit. We created a perfect square on the left hand side, so let's write it as a perfect square:

(x + 1)

^{2}= 4Take the square root of both sides

x + 1 = ± 2

subtract 1 from both sides

x= + 2 -1 = 1

x = -2 -1 = -3

Mary Ann F.

^{2}- 4ac01/18/15